Expanding the phenotypic spectrum associated with CFAP43 mutations: a case report of familial male infertility with respiratory manifestations - Awad, Fawaz; Abukhaizaran, Razan; Al Jabi, Shahira; Nabilsi, Mustafa; Ayasa, Laith A.; AbuAlrob, Majd A.; Owienah, Haneen; Kassem, Hanin; Kanaan, Moien (Frontiers in Reproductive Health, 2025)
AimsMultiple morphological abnormalities of the sperm flagella (MMAF) represents a rare and severe form of male infertility, characterized by defects in sperm flagella. Mutations in genes essential for flagellar function, such as CFAP43, have been implicated in MMAF. Flagella and motile cilia share a conserved axonemal structure essential for their motile function and the asthenospermia-related infertility of MMAF overlaps with primary ciliary dyskinesia (PCD) symptoms, characterized by chronic airway disease and infertility due to ciliary and flagellar dysfunction. This study investigates the genetic basis of MMAF in two siblings, who also exhibited respiratory symptoms.MethodsClinical assessment and semen analysis were conducted for two brothers presenting with infertility and chronic respiratory symptoms. Whole-exome sequencing (WES) was performed to identify potential genetic defects.ResultsBoth siblings exhibited classic MMAF features, including asthenospermia with various flagellar abnormalities, in addition to chronic respiratory symptoms including sinusitis and wet cough. WES identified a novel homozygous missense genetic variation in CFAP43 [c.421T>A p.(Trp141Arg)].ConclusionOur findings provide additional evidence of the genetic contribution of CFAP43 in MMAF and suggest an expanded phenotypic spectrum of CFAP43-associated conditions to encompass chronic respiratory symptoms attributed to airway ciliary dysfunction. Further research is needed to uncover the underlying mechanisms linking CFAP43 mutations to these phenotypes.